Description of a new Filchneria (Plecoptera: Perlodidae), with supplementary illustrations for Taenionema japonicum (Plecoptera: Taeniopterygidae) from northeastern China - Chen, Zhi-Teng (Zootaxa, 2020)
A new species of the perlodid genus Filchneria Klapálek, F. dongruihangi sp. nov. is described and illustrated based on male and female from Heilongjiang Province of northeastern China. The new species is distinctive by the unique shape of female subgenital plate. Morphological comparisons are provided with related taxa. In addition, the taeniopterygid species, Taenionema japonicum (Okamoto) was collected from Jilin Province of northeastern China and supplemented with new illustrations.